A Theory and Process Evaluation of the Umhlathuze Water Stewardship Programme of the International Water Stewardship Programme - Gautier, Estelle (School of Management Studies, 2020)
Water is a scarce resource without which human survival is at risk and major economies would collapse if not carefully managed. Water stewardship involves collaboration between role players from the public- and private sector as well as civil society to effectively mitigate some of the water related risks and improve water security. Good practice examples of water stewardship have been captured in only a limited number of international studies through the work of a few organisations driving adoption of stewardship practices. Most of these are internal documents and remain unpublished. There are a few local, unpublished studies that are specific to water stewardship as an approach to water resources management in South-Africa. A comprehensive literature review on water resource management institutions in South published between 1997 and 2011, shows that research is predominantly focused on catchment management agencies (CMA) than on other entities such as international water management bodies, water user associations or water irrigation boards (Meissner, 2013) The uMhlathuze Water Stewardship Programme (UWaSP) is a South African programme selected to evaluate if the programme has been established against globally recognised good practices of water stewardship and to what extent it has been implemented accordingly. The programme is part of an international water stewardship programme which provided an ideal opportunity to evaluate a local programme against a global good practice model. The international literature on water stewardship as well as literature on adaptive co-management approaches to water resources management enabled the development of a consolidated global good practice evaluation model of water stewardship. The research included consideration of contextual influences that may have enabled or hindered the implementation of the establishment of the water stewardship programme. The South African literature shows that a specific type of integrated water resources management ( IWRM) , catchment management associations (CMA’) share certain adaptive co-management elements with a water stewardship approach to water management. These include three concepts extracted from the literature namely collaborative stakeholder engagement, adaptation through learning (experimentation) as well as a bioregional approach to water resources management which means implementation of management structures at the river basin level (Meisner, 2016). The local contextual factors influencing implementation of the UWaSP and commonalities with CMA’s are considered during the discussion, against the background of the findings of local studies.